ALANIN AMINOTRANSFERASE, ASPARTAT AMINOTRANSFERASE LEVELS AND HEPAR HISTOLOGICAL OF RATTUS NORVEGICUS WITH MUSA PARADISIACA FORMATYPICA PEEL EXTRACT AND INTENSIVE EXERCISE - Prasetyawan, Putu Angga; Suarsana, I Nyoman; Kendran, Anak Sagung (Buletin Veteriner Udayana, 2021)
Body activities such as excessive intensive exercise causes the body to need very much oxygen, triggering the emergence of free radicals that can damage various organs; one of them is the liver. In order to prevent damage to liver cells due to free radicals, efforts are needed to provide antioxidant intake from the outside. One of them is musa paradisiaca formatypica peel. The study was conducted to determine changes in ALT levels (Alanin Aminotransferase), AST (Aspartat Aminotransferase), and histology description of white rat liver that was given musa paradisiaca formatypica peel extract and intensive physical exercise. Twenty-seven rats were divided into three groups. The treatment was given for 28 days. Next, blood and liver samples were taken on the 29th day. Blood samples were tested using the photometric method, while liver samples were examined through histological preparations with staining method hematoxylin-eosin (HE). The research data were tested using variance (ANOVA) and continued with test Duncan. The results showed the administration of musa paradisiaca formatypica peel extract to white rats given intensive swimming training significantly reduced levels of ALT, AST and could reduce the occurrence of liver degeneration and necrosis. The results of the study concluded that musa paradisiaca formatypica peel extract can prevent liver damage due to intensive physical exercise.